Aloe-emodin: from pharmacological mechanisms to clinical applications and future perspectives - Xie, Jin; Zhang, Junfeng; Chen, Xiaoyan (Frontiers in Pharmacology, 2026)
Natural products continue to be fundamental to contemporary drug discovery. Aloe-emodin, a natural anthraquinone molecule sourced from plants including aloe and rhubarb, has attracted considerable interest owing to its diverse pharmacological properties. This review analyzes the complex modes of action of AE, emphasizing its significant anti-cancer effects by targeting critical signaling pathways like PI3K/Akt, MAPK, and NF-κB, which induce apoptosis and cell cycle arrest, regulate autophagy, and inhibit metastasis. In addition to oncology, AE exhibits potent anti-inflammatory, neuroprotective, and antiviral effects primarily by reducing oxidative stress and regulating inflammatory responses. Notwithstanding its encouraging preclinical performance, the practical application of AE has been impeded by considerable obstacles, notably its inadequate bioavailability, possible toxicity, and absence of target selectivity. We rigorously assess these challenges and examine novel tactics designed to improve its therapeutic index, including nanotechnology-based drug delivery devices and alterations to chemical structures. This review seeks to reconcile the intricate pharmacology with clinical applicability, offering a prospective outlook on the use of AE as a next-generation therapeutic agent for cancer and other complex disorders.